(untitled) (Journal of the College of Education for Women, 2017)
Language is an important means through which one can construct one’s social world. Accordingly, the way we view ourselves and the world is basically formed by language use whereby identities, relations, and values are constructed and maintained. Most discourse analysts consider narrative not only the locus of construction and enactment of identity, but also a distinguished genre for its analysis.The present study is concerned with how identity can poetically be informed, hence exploring the way black poets use language when reflecting their identity and culture. The poem, right on: white america by the black American poetess Sonia Sanchez, is chosen to be analyzed based on Simpson’s stylistic model (2004). In this model, the analysis of the levels of language shapes and organizes the stylistic analysis whereas discourse is situated above the central levels of language. Stylistics and discourse analysis aim to show how and why the text means what it means linguistically. The study concludes that poetry is a potent creator and an enforcer of identity. The stylistic analysis casts light on the linguistic deviations, especially on the graphological level used by the poetess Sonia Sanchez. Such a level expresses the poetess’ resistance and rage against the white. Besides, Sonia Sanchez’s use of Black English transmits her belonging to the oppressed Black.